Phase Separation in Biology and Disease; Current Perspectives and Open Questions. Issue 5 (1st March 2023) - Boeynaems, Steven; Chong, Shasha; Gsponer, Jörg; Holt, Liam; Milovanovic, Dragomir; Mitrea, Diana M.; Mueller-Cajar, Oliver; Portz, Bede; Reilly, John F.; Reinkemeier, Christopher D.; Sabari, Benjamin R.; Sanulli, Serena; et al.
Graphical abstract: Highlights: Phase separation underlies formation of myriad biomolecular condensates in cells. Biomolecular condensates are associated with diverse biological functions. Questions surrround causal relationships between phase separation and function. Aberrant phase separation is associated with human disease. Targeted therapeutics against aberrant condensates hold promise for future. Abstract: In the past almost 15 years, we witnessed the birth of a new scientific field focused on the existence, formation, biological functions, and disease associations of membraneless bodies in cells, now referred to as biomolecular condensates. Pioneering studies from several laboratories [reviewed in 1–3 ] supported a model wherein biomolecular condensates associated with diverse biological processes form through the process of phase separation. These and other findings that followed have revolutionized our understanding of how biomolecules are organized in space and time within cells to perform myriad biological functions, including cell fate determination, signal transduction, endocytosis, regulation of gene expression and protein translation, and regulation of RNA metabolism. Further, condensates formed through aberrant phase transitions have been associated with numerous human diseases, prominently including neurodegeneration and cancer. While in some cases, rigorous evidence supports links between formation of biomolecular condensates through phase separation and biological functions, in many others such links are less robustly supported, which has led to rightful scrutiny of the generality of the roles of phase separation in biology and disease. 4–7 During a week-long workshop in March 2022 at the Telluride Science Research Center (TSRC) in Telluride, Colorado, ∼25 scientists addressed key questions surrounding the biomolecular condensates field. Herein, we present insights gained through these discussions, addressing topics including, roles of condensates in diverse biological processes and systems, and normal and disease cell states, their applications to synthetic biology, and the potential for therapeutically targeting biomolecular condensates.